MOTIVATION OF INDIAN CONSUMERS TO CHOOSE INTERNATIONAL LUXURY BRANDS - Chandna, Shridhar (2015)
This dissertation seeks to ascertain the motivations of Indian consumers towards the purchase of International luxury brands, the significance of luxury in the Indian markets, interpersonal and personal motivations to purchase International luxury brands’ products and the influence of Indian culture on the luxury purchase motivation. The research process was conducting using in-depth interviews and followed an interview guide. Fourteen Indian participants were involved in the interviews and the snowball sampling technique was applied. This research adopted thematic analyses to analyze the interview results. The research primarily concentrates on luxury consumption motivation: interpersonal and personal motivation and Indian culture. As India opened its economy for International trade and investment, followed by a rapid growth in the economy, the impact of Globalization has increased significantly than it used to be on Indian culture and hence Indian consumers now have different motivations towards purchasing International luxury brands. Therefore, this research aims to understand the main motivations of Indian consumers and the influence of Indian culture on their purchase decisions.